2015
DOI: 10.1098/rstb.2014.0121
|View full text |Cite
|
Sign up to set email alerts
|

Artificial light at night: melatonin as a mediator between the environment and epigenome

Abstract: The adverse effects of excessive use of artificial light at night (ALAN) are becoming increasingly evident and associated with several health problems including cancer. Results of epidemiological studies revealed that the increase in breast cancer incidents co-distribute with ALAN worldwide. There is compiling evidence that suggests that melatonin suppression is linked to ALAN-induced cancer risks, but the specific genetic mechanism linking environmental exposure and the development of disease is not well know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
74
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(77 citation statements)
references
References 95 publications
2
74
0
1
Order By: Relevance
“…With regard to effects of melatonin in both the circadian and the immunological fields, epigenetic effects of exogenous melatonin are highly likely. Although this possibility has been addressed in the context of LAN [135], the direct evidence in humans is actually insufficient for any robust judgment.…”
Section: Resultsmentioning
confidence: 99%
“…With regard to effects of melatonin in both the circadian and the immunological fields, epigenetic effects of exogenous melatonin are highly likely. Although this possibility has been addressed in the context of LAN [135], the direct evidence in humans is actually insufficient for any robust judgment.…”
Section: Resultsmentioning
confidence: 99%
“…DNA methylation is a common and an important epigenetic pathway for regulating gene expressions in response to environmental signals (Jaenisch & Bird, 2003 suppressor genes and metastatic genes that are responsible for mediating carcinogenic activity from early to terminal stages of tumor progression (Day & Bianco-Miotto, 2013;Hattori & Ushijima, 2014;Xiang et al, 2013). In a recent review, we have suggested a possible mechanism for ALAN-induced cancer development (Haim & Zubidat, 2014). Accordingly, the ALAN-induced melatonin suppression stimulates oncogenes and inhibits tumor suppressor genes by genomic regulation of aberrant DNA methylation resulting in tumor progression.…”
mentioning
confidence: 97%
“…Supportively, a recent review of the signaling pathway linking between the ALAN-induced MLT suppression and breast cancer progression in human and non-human models, has implied the occurrence of epigenetic modifications, particularly GDM as a potential molecular mechanism linking environmental exposures (e.g. ALAN) and adverse health outcomes [219]. According to this review, MLT levels are regulated by ipRGCs, which control the inhibition of the pineal hormone in response to short wavelength ALAN and consequently advance tumorigenesis mediated by epigenetic modification, such as DNA methylation.…”
Section: Mlt and Epigenetic Modificationsmentioning
confidence: 99%
“…According to this review, MLT levels are regulated by ipRGCs, which control the inhibition of the pineal hormone in response to short wavelength ALAN and consequently advance tumorigenesis mediated by epigenetic modification, such as DNA methylation. Considering the suggested association between obesity and the development of variant cancers [220], the suggested nexus between ALAN, MLT suppression, epigenetic modifications, and adverse health consequences [219] is of significant clinical importance.…”
Section: Mlt and Epigenetic Modificationsmentioning
confidence: 99%